Self-Isolation during the COVID-19 Pandemics: Everyday Discourse on a New Social Phenomenon among University Students - Novikova, Irina A.; Novikov, Alexey L.; Sachkova, Marianna E.; Dvoryanchikov, Nikolay Viktorovich; Berezina, Elizaveta *; Bovina, Inna Borisovna (RUDN University, 2024)
The COVID-19 pandemic was the first experience for the largest part of the world’s population of a new disease that spread rapidly across continents, a global threat to which unprecedented restrictive measures were elaborated. The purpose of the study was to analyse the everyday discourse on self-isolation among student youth based on the Theory of Social Representations. The study was conducted in two time periods corresponding to two “waves” of the COVID-19 pandemic in Russia (“first wave”: from 18, June to 10, July, 2020, and “second wave”: from 12, October to 18, November, 2020). The sample included 275 Russian university students (9.5 % male) aged 17 to 27 years. The main tool to reveal the social representations was free associations technique. The survey was conducted in online format via Google-forms. Comparison of the structure and content of social representations on self-isolation as a new social phenomenon at different stages of the pandemic made it possible to reveal their emergence and dynamics among student youth: (1) the opposition between voluntariness and coercion was characteristic of the everyday understanding of selfisolation at the very beginning of the pandemic, and (2) psychological experiences associated with the pandemic and the self-isolation caused by it turn out to be key further. In general, research findings show that self-isolation is understood by university students as a search for “pluses” in a situation of forced restrictions.